Editorial: severe outcomes are rare in pregnancy in autoimmune hepatitis—Authors' reply. Issue 9 (14th October 2018) - Grønbæk, Lisbet; Vilstrup, Hendrik; Jepsen, Peter
Abstract : Linked Content This article is linked to Grønbæk et al and Hagstrom and Ludvigsson papers. To view these articles visit https://doi.org/10.1111/apt.14925 and https://doi.org/10.1111/apt.14957 .